PENGEMBANGAN TEPUNG PALADO (Aglaia sp.) SEBAGAI PANGAN ALTERNATIF DARI HUTAN - Syamsul Rahman; Awaluddin Rauf; A. Susilawaty Hardiani (Jurnal Penelitian Hasil Hutan, 2021)
Palado seeds (Aglaia sp.) are originally part of wild forest plants commonly used as a snack by boiling and roasting. Theutilization of these seeds into flour increases its value and extends the storage time as an alternative food ingredient. Therefore, thisstudy aimed to analyse the macronutrient content of palado flour by proximate anlysisi. Parameter analysed includes moisture ash,fat, protein, carbohydrate, and energy contents the palado flour. Analysis of moisture content was determined by drying method; ashcontent was determined by ashing in a furnace; fat content was determined by soxhlet method, protein was determined by the MicroKjeldahl method, carbohydrate content was determined by weight talce, and energy content was determined by the sum of the weightof crude protein, carbohydrates, and fat. The results showed that the palado flour consisted of 66.72% carbohydrate, 12.37% fat,3.61% ash, and 414kcal energy. This research indicates that palado flour could be an alternative flour, both as the main foodmaterial and as a fortification palado seeds, alternative food, nutrition content, flour, bread and noodles.